2019
DOI: 10.1097/nna.0000000000000738
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Generational Considerations in RN Retention

Abstract: OBJECTIVE The aim of this study was to identify evolving cultural and generational factors influencing nurse retention. BACKGROUND Multigenerational/culturally diverse workforces challenge the nurse leader's understanding of nurse satisfaction. METHODS A survey was designed to identify the RN's career intentions, desired leadership traits, and practice environment appraisal. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 19 publications
1
37
1
1
Order By: Relevance
“…Millennials expressed that supportive leadership helped them to feel positive about their work and grow in their professional role. Previous findings are similar to those in this study, citing that support from nurse leaders was closely tied to job satisfaction and retention of millennials (Andrews, 2013; Dols, Chargualaf, & Martinez, 2019; Faller & Gogek, 2019; Gordon, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Millennials expressed that supportive leadership helped them to feel positive about their work and grow in their professional role. Previous findings are similar to those in this study, citing that support from nurse leaders was closely tied to job satisfaction and retention of millennials (Andrews, 2013; Dols, Chargualaf, & Martinez, 2019; Faller & Gogek, 2019; Gordon, 2017).…”
Section: Discussionsupporting
confidence: 86%
“…Two studies reported Baby Boomer nurses find autonomy important to their nursing practice (Gordon, 2017; Lipscomb, 2010). For managers/leadership, Baby Boomers preferred leaders who were supportive, professional (Wieck et al, 2010), trustworthy (Dols, Chargualaf, & Martinez, 2019; Wieck et al, 2010) and empowering, had integrity and had ‘good reasoning skills’ (Dols et al, 2019, p. 205). Gordon (2017) reports that all generations, including Baby Boomers, prefer senior leadership at a hospital to have a background in medicine or nursing rather than business.…”
Section: Resultsmentioning
confidence: 99%
“…Autonomy (Dols et al, 2010; Gordon, 2017; Lipscomb, 2010), number of tasks (Gordon, 2017) and communication (Whitmer et al, 2009) were all reported values of Generation X. Generation Xers want a manager who is supportive, a team player and dependable (Wieck et al, 2010), can reason well, is trustworthy, has integrity and serves as a mentor (Dols et al, 2019). They also have a favourable opinion of senior leadership having a background in medicine or nursing (Gordon, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment and retention of registered nurses in all health care organizations is cited as the greatest challenge threatening patient care (Dols, Chargualaf, & Martinez, 2019). While this involves the retirement of “baby boomers,” there is also another area of attrition.…”
mentioning
confidence: 99%